The role of school leaders in adopting the digital citizenship project - Al - Otaibi, Mashael Asir (Journal of Educational and Psychological Sciences, 2018)
The present study aims to identify the role of school leaders in strengthening the values ​​of digital citizenship in students from their point of view and identify the obstacles that guide school leaders in activating digital citizenship and revealing the obstacles facing the leaders of schools in activating the values ​​of digital citizenship in students and then make a set of proposals To activate the role of school leaders in strengthening the values ​​of digital citizenship. The researcher used the descriptive analytical method. To achieve the objectives of the study, a questionnaire was prepared by the researcher, consisting of (45) paragraphs. Which were applied to a simple random sample that included (70) director of the study society (191) leader. The study reached the following results: Evaluation of the sample of the educational leaders for the role of school leaders in the development of digital citizenship among the educated. And that the difficulties faced by female leaders in activating the values ​​of digital citizenship lies in the multiplicity of roles and tasks of the educational leader within the school. The study found that there are no statistically significant differences at the level of 0.05 or less in the responses of members of the study community on the three axes of the study in terms of years of experience and training courses In addition, suggestions were made to activate digital citizenship by incorporating the curricula and curricula of the school to enhance the citizenship of the students. Based on the results of the study, the researcher presented some recommendations for raising the skills of school leaders in activating digital citizenship among female students.